Molecular Understanding of the Cardiomodulation in Myocardial Infarction and the Mechanism of Vitamin E Protections - Zarkasi, Khairul A.; Jen-Kit, Tan; Jubri, Zakiah (Mini Reviews in Medicinal Chemistry, 2019)
Myocardial infarction is a major cause of deaths globally. Modulation of several molecular mechanisms occurs during the initial stages of myocardial ischemia prior to permanent cardiac tissue damage, which involves both pathogenic as well as survival pathways in the cardiomyocyte. Currently, there is increasing evidence regarding the cardioprotective role of vitamin E in alleviating the disease. This fat-soluble vitamin does not only act as a powerful antioxidant; but it also has the ability to regulate several intracellular signalling pathways including HIF-1, PPAR-γ, Nrf-2, and NF-ΚB that influence the expression of a number of genes and their protein products. Essentially, it inhibits the molecular progression of tissue damage and preserves myocardial tissue viability. This review aims to summarize the molecular understanding of the cardiomodulation in myocardial infarction as well as the mechanism of vitamin E protection.
Keywords: Myocardial infarction